2011
DOI: 10.1071/wf09082
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic and biotic influences on Bromus tectorum invasion and Artemisia tridentata recovery after fire

Abstract: Native sagebrush ecosystems in the Great Basin (western USA) are often invaded following fire by exotic Bromus tectorum (cheatgrass), a highly flammable annual grass. Once B. tectorum is established, higher fire frequencies can lead to local extirpation of Artemisia tridentata ssp. vaseyana (mountain big sagebrush) and have cascading effects on sagebrush ecosystems and the species that depend on them. We conducted a landscape-scale observational study to examine the distribution and cover of B. tectorum and A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 35 publications
5
88
0
1
Order By: Relevance
“…vaseyana in 2009 was approximately the same on Phase 2 and 3 sites, so we might expect that future recovery will be similar. However, Condon et al (2011) indicated that re-establishment of A. tridentata following fire is positively related to cover of perennial herbaceous species. This relationship may influence the rate and magnitude of A. t. ssp.…”
Section: Shrub Recoverymentioning
confidence: 99%
See 4 more Smart Citations
“…vaseyana in 2009 was approximately the same on Phase 2 and 3 sites, so we might expect that future recovery will be similar. However, Condon et al (2011) indicated that re-establishment of A. tridentata following fire is positively related to cover of perennial herbaceous species. This relationship may influence the rate and magnitude of A. t. ssp.…”
Section: Shrub Recoverymentioning
confidence: 99%
“…This level of perennial grasses was adequate for density to recover 4 years after fire and, in combination with higher densities of perennial forbs than that on Phase 3 sites, likely limited B. tectorum increases on Phase 2 sites. Others have indicated that greater presence and recovery of perennial herbaceous vegetation prevents annual grasses from dominating after fire in sagebrush steppe (Chambers et al 2007;Davies et al 2008;Bates and Svejcar 2009;Bates et al 2011;Condon et al 2011). Another element that may have supported native plant recovery on the Phase 2 sites was, potentially, a more complete soil seed bank.…”
Section: Herbaceous and Ground Cover Responsementioning
confidence: 99%
See 3 more Smart Citations